(3GdGWaGd GhdkG (B- (3GJaGbjI Mbhb GdWad s (3GdGYdGf GdYGdej dHbGA GdWad hMeGjJg hfeGFg hNWI GdYed s (**** UNICEF, 1997)
(3agQS(B.s
(3YGe (B1990 (3GLfeY GcHQ MTO ef bGOI Ohd GdYGde bj ebQ GdGee GdeJMOI HfjhjhQc defGbTI LOhd GYeGd echf ef HfO hGMO, gh GdGWaGd(B. (3haj NJGe Jdc GdbeI JHfi hGMO hSHYhf ef RYeGA Ohd GdYGde hQDSGA GdMcheGJ GVGaI Gdi JeGfjI hKeGfjf eeKdkG QSejkG BNQ eYXege HeQJHI hRQGA GYdGfkG HGdGdJRGe HHbGA GdWad hMeGjJg hJfejJg hNWI Yed dJfajP HfhO Pdc GdGYdGf(B.s
Keywords: Droits de l'enfant